Bahasa Inggris - Fauzan Reza Fahlevi; Roshim Ahmad Musyaffa; Rahmahdalena Putri Khairunnisa; Zaitun Qamariah; Hesty Widiastuty (Universitas Veteran Bangun Nusantara, 2026)
Students at MTs Hidayatul Insan experience difficulties in understanding spoken English due to conventional listening instruction that provides limited visual support and low engagement. To address this issue, a community service program was implemented using digital animation integrated with games, dialogues, and role-playing activities. The program aimed to integrate digital animation media and interactive teaching methods into English listening instruction while encouraging student participation and classroom engagement. Participants were ninth-grade students at MTs Hidayatul Insan. Data were collected through classroom observations, student feedback, and documentation and were analyzed descriptively. The findings indicate that digital animation provided visual and auditory support that encouraged students’ engagement with listening materials and promoted classroom participation. Furthermore, games, dialogues, and role-playing activities encouraged active participation, interaction, and meaningful language use. Overall, students demonstrated positive responses, high enthusiasm, and active involvement throughout the learning activities. The program demonstrates that the integration of digital animation media and interactive teaching methods can create a more engaging environment for English listening instruction in EFL classrooms.